ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH ON CONSUMER PREFERENCE IN HOTEL SELECTION DURING COVID-19 PANDEMIC (CASE STUDY: NOVOTEL HOTEL, SWISS BELL HOTEL, FOUR POINTS HOTEL) - Amelinda Nathania Veren Kindangen; Merinda Pandowo (Universitas Sam Ratulangi, 2022)
The hospitality industry is one of the most significant contributions to the Indonesian economy. In Manado, the impact of the Covid 19 pandemic resulted in the tourism industry, especially the hotel business being very down. The purpose of this study was to determine the most preferred hotel among the three hotels (Novotel, Swiss Bell, and Four Points). And what criteria most influenced respondents to stay at the three hotels using the Analytical Hierarchy Process method. This type of research approach is a quantitative method. The population in this study is people in Manado who have stayed and have experience with Novotel, Swiss Bell, and Four Points.Hotel criteria mean factors of the hotel are Price, Place, Customer Satisfaction, Advertisement, Peer Influence. Based on the result and discussion, two conclusions can be formulated, Place is the criterion that influences the most in selecting a hotel. Four Points is the most chosen hotel in Manado, Four Points became the most preferred hotel because it excels in four criteria; place, advertising, customer satisfaction, and peer influence. And in the second position is Novotel, and Swiss Bell is in the last position.Â Keywords: Consumer Preference, Hotel Selection